2020
DOI: 10.1038/s41467-020-14928-3
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis confers resistance to therapies targeting cancer anabolism

Abstract: Macropinocytic cancer cells scavenge amino acids from extracellular proteins. Here, we show that consuming necrotic cell debris via macropinocytosis (necrocytosis) offers additional anabolic benefits. A click chemistry-based flux assay reveals that necrocytosis provides not only amino acids, but sugars, fatty acids and nucleotides for biosynthesis, conferring resistance to therapies targeting anabolic pathways. Indeed, necrotic cell debris allow macropinocytic breast and prostate cancer cells to proliferate, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 73 publications
2
104
0
1
Order By: Relevance
“…These results are consistent with our observations on utilization of the GlcNAc salvage pathway to fuel UDP-GlcNAc pools from HA-derived GlcNAc (Figure 4E). Our study also contributes to a growing body of data illuminating unexpected nutrient sources in the TME that support cancer metabolism (13,14,(16)(17)(18)(19)(20)(21)47), and this raises the possibility that other glycosaminoglycans may be similarly scavenged.…”
Section: Discussionmentioning
confidence: 64%
“…These results are consistent with our observations on utilization of the GlcNAc salvage pathway to fuel UDP-GlcNAc pools from HA-derived GlcNAc (Figure 4E). Our study also contributes to a growing body of data illuminating unexpected nutrient sources in the TME that support cancer metabolism (13,14,(16)(17)(18)(19)(20)(21)47), and this raises the possibility that other glycosaminoglycans may be similarly scavenged.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, CTP1 inhibitors can be used to both reduce lipid decomposition and reduce energy support for tumors. Moreover, another energy supply method called the giant cell drinking process has been found to be resistant to drug action [ 60 ]. Macrophages take up necessary biological materials from dead tumor cell fragments through endocytosis.…”
Section: Lipids and Drug Resistance In Cancersmentioning
confidence: 99%
“…PI3K regulates the actin cytoskeleton through Rac1 and promotes the closure of a large body through phosphoinositide signal [ 62 ]. The phagocytized necrotic cells are decomposed and metabolized to provide energy for tumor cell proliferation ( Figure 2 ) [ 38 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Lipids and Drug Resistance In Cancersmentioning
confidence: 99%
“…There are a number of mouse cell lines that lead to tumor formation and metastasis such as 4T1, B16, Lewis lung carcinoma cells, Met-1, and RM1 [66]. It was recently reported using orthotopic injection of 4T1 mouse mammary tumor cells (generated from CARMIL1-WT or CARMIL1-AA cells) into BALB/c mice to study the role of macropinocytosis in mediating treatment resistance [68]. They found that macropinocytosis fuels tumor growth (possibly by generating intracellular cell nutrients such as amino acids, sugars, fatty acids, and nucleotides via necrocytosis) and increases resistance to 5-FU [68].…”
Section: Metastasismentioning
confidence: 99%